Regulatory T Cells as a Novel Candidate for Cell-Based Therapy in Kidney Disease - Lu, Junyu; Zhang, Jianfeng; Chen, Menghua; Chen, Chun; Li, Zhengzhao; Liao, Pinhu (Frontiers in Physiology, 2020)
Kidney disease is a significant health concern worldwide. Ineffective treatment can lead to disastrous consequences, such as organ failure and death. Research has turned to cell-based therapy, but has yet to produce an effective and reliable treatment for kidney disease. To address this problem, we examined four datasets of gene expression profiles from diseased and healthy kidney tissue in humans, mice, and rats. Differentially expressed genes were screened and subjected to enrichment analyses. Up-regulated genes in diseased kidney tissue were significantly enriched in pathways associated with regulatory T cells (Tregs). Analysis with the xCell tool showed that Tregs were generally increased in diseased kidney tissue in all species. To validate these results in vivo, kidneys were removed from mice with Adriamycin-induced nephropathy, and histology confirmed increase of Tregs. Furthermore, Tregs were adoptively transferred from healthy mice into mice with kidney injury, restoring normal structure to the damaged kidneys. Treg cells that were co-cultured with M2c macrophages exhibited up-regulation of chemokine receptors CCR2, CCR5, CCR7, CD62L, and CX3CR1. This may be the mechanism by which M2c cells enhance the migration of Tregs to the site of inflammation. We propose that Tregs may be an effective, novel candidate for cell-based therapy in pre-clinical kidney injury models.